Transforming Inclusive Digital Pedagogy in Malaysian Tertiary TVET: Adapting to a New Educational Landscape - Mohd Ridhuan bin Mohd Jamil, Mohd Muslim bin Md Zalli, Nik Muhammad Hanis bin Nek Rakami (Tanjung Malim, 2024)
Transforming Inclusive Digital Pedagogy in Malaysian Tertiary TVET: Adapting to a New Educational Landscape by Mohd Ridhuan bin Mohd Jamil, Mohd Muslim bin Md Zalli, Nik Muhammad Hanis bin Nek Rakami